Health Equity and Social Determinants: Integrating Principles into Public Health Management - Wilson Lukose, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper discuss about how important it is for public health management to take into account health fairness ideals and social factors. There are still differences in health around the world, which are caused by complicated relationships between social, economic, and natural factors. To successfully deal with these differences, public health management needs to take a broad approach that looks at the root factors that affect health results. This essay takes a look at recent studies and models to show how health equity principles and social factors can be used in public health management. This shows how important it is to know why some people have worse health than others and work together with people from different fields to fix the problem. It also looks at how policy changes, community involvement, data-driven decision-making, and changes to the health system can all help improve health fairness. Policymakers, practitioners, and other interested parties can help reduce health gaps and improve community health results by incorporating these ideas into public health management.